Environmental Degradation and the Compromise of Transportation Networks in the Niger Delta. - Worlu, Heoma Nsirim (Advances in Social Sciences Research Journal, 2015)
The action of man in the process of producing material goods for his subsistence has caused serious alteration in the biodiversity as deleterious or hazardous substances are released into the environment. Man and his products move from one spot to the other by network of mobility which is described as transportation network. There are varied means of mobility, some faster than others and each is powered by oil and oil related products. Crude oil is found in large scale in the Niger Delta region of Nigeria; and the processes of production, transportation and utilisation have been compromised and there are observable avoidable accidents and sufferings; these are accounted for by way of hike in the cost of the powering agents, scarcity, pirates, conflicts and even militancy. With proper and quality education; and conscientising of people on the security of the environment and the means of movement, the officials whose duty it is to maintain standards will perform efficiently and effectively and the people on the other hand will cease to be channels through which the environment will be degraded. This is done by examining the role of the institutions that are charged with regulating transportation in the region; the causes and sources of environmental degradation are investigated. The Niger Delta environment is reviewed briefly so that the readers will understand the link between the environment, production process and the movement of finished goods, services and humans; and why the three elements should be handled carefully.